On Promise and Fulfillment: A Narrative Analysis of John 2:1-12 and John 19:16b-42 - Zhang, Yu Zhe (Cecilia) (Université d'Ottawa | University of Ottawa, 2024)
This thesis uses narrative criticism to analyze two narratives from the Gospel of John, with a focus on how the setting and narration, plot, characters, and literary devices work together to convey the central themes of the Gospel. The narrative of the wedding at Cana found in John 2:1-12, as the first sign performed by Jesus in his public ministry, is replete with themes that are only fulfilled in the glorification of Jesus on the cross in John 19:16b-42. Together, as the first and last of the signs performed by Jesus in the Fourth Gospel, the two narratives depict the theological themes of the glorification of Jesus, the eschatological banquet of the kingdom, the gift of the Spirit, the birth of the church, and new creation. Cette thèse utilise la critique narrative pour analyser deux récits dans l’Évangile de Jean, particulièrement la façon dont le cadre et la narration, l’intrigue, les personnages et les dispositifs littéraires contribuent à transmettre les thèmes centraux de l’Évangile. Le récit des noces de Cana qui se trouve dans Jean 2,1-12, en tant que premier signe accompli par Jésus dans son ministère public, regorge de thèmes qui se réalisent seulement à la glorification de Jésus sur la croix dans Jean 19,16b-42. Ensemble, comme premier et dernier signes accomplis par Jésus dans le Quatrième Évangile, les deux récits décrivent les thèmes théologiques de la glorification de Jésus, du banquet eschatologique du royaume, du don de l’Esprit, de la naissance de l’Église, et de la nouvelle création.